Violência contra a mulher: proposta para a elaboração do plano municipal de enfrentamento e proteção de mulheres em situação de violência em uma cidade do sul de Minas Gerais - Lima Junior, Aloísio Soares de (2021)
Violence against women has been a largely debated issue between civil society and the state concerning the responsibility of carrying out and implementing protective measures policies, capacitating and creating mechanisms of assistance to women. In this regard, the present proposal aims to rescue a theoretical and historical record of women in situation of violence, pointing out policies and strategies to combat it. The debate emerges from an exponential raise in the number of women victims of violence and a great need for inserting victims’ demands into the governmental agendas. The scope of this work is to tackle the phenomenon of violence against women, establishing the connections between several concepts that clarify this social anomaly, proposing to implement a public policy at the local government level, aiming to reduce cases and the perpetuation of this chauvinist and archaic practice. The methodology used in the project is the descriptive research and case study techniques, on-site, carried out with local government managers and other social protection agents; besides documentary analysis obtained via information systems from protective organs associated with this topic, identifying the amount of incidences of violence in the city and the arrangements of public policies already consolidated. This project brings as theoretical reference perspectives on Gender and Patriarchy, the intersectional relations between Gender, Rank and Race from the perspective of violence, also trying to elucidate the concepts and kinds of violence against women, as well as the importance of Public Policies in the municipal sphere.